Positive electrode lithium supplementing agent, preparation method thereof, positive electrode sheet and battery

CN122677447APending Publication Date: 2026-09-01JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610969791.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-09-01

AI Technical Summary

Technical Problem

[0003]现有的正极内置预锂化试剂存在化学稳定性差的缺陷,在空气中暴露后,其结晶度和电化学性能显著下降,导致其在实际应用中受到限制,从而难以大规模生产和应用

Benefits of technology

在本申请实施例中,对正极补锂剂的组成进行优化,解决了常规使用的富锂铁酸锂存在的环境敏感度过高的问题,以及单独使用富锂钴酸锂成本较高的问题。首先,通过第一包覆层提升正极补锂剂的电化学性能、减少化成时间,从而提升电池的生产效率;其次,第一包覆层中的富锂钴酸锂或钴铁互溶体的富锂氧化物物相能提升正极补锂剂的结构稳定性,提升正极补锂剂的环境稳定性和降低正极补锂剂长期产气情况,提升正极补锂剂的安全性能;再次,还通过第二包覆层进一步提升正极补锂剂的环境稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122677447A_ABST
    Figure CN122677447A_ABST
Patent Text Reader

Abstract

This invention relates to the field of battery technology, specifically to a positive electrode lithium replenisher and its preparation method, a positive electrode sheet, and a battery. The positive electrode lithium replenisher comprises: a core, the core including a first lithium replenisher comprising a lithium-rich material with an anti-fluorite structure; a first coating layer covering at least a portion of the surface of the core, the first coating layer including a second lithium replenisher comprising a cobalt-containing lithium-rich material with an anti-fluorite structure; and a second coating layer covering at least a portion of the surface of the first coating layer, the second coating layer comprising a metal compound; wherein the specific capacity of the second lithium replenisher is higher than that of the first lithium replenisher. This positive electrode lithium replenisher has the advantages of good chemical stability and can be mass-produced and applied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically, to a positive electrode lithium replenishing agent and its preparation method, a positive electrode sheet, and a battery. Background Technology

[0002] Lithium-ion batteries (LIBs) are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density, long cycle life, and good rate performance. However, existing LIBs form a solid electrolyte interphase (SEI) film during the first charge and discharge cycle, consuming a large amount of active lithium ions and resulting in low coulombic efficiency in the first cycle. Furthermore, cracking of the positive electrode active material particles, thickening and repair of the SEI film also consume active lithium ions, leading to a decline in battery cycle performance. To compensate for lithium ion loss during the first cycle, pre-lithiation technology has been proposed and widely applied. Existing pre-lithiation technologies mainly include anode pre-lithiation and cathode pre-lithiation. Anode pre-lithiation is usually achieved by adding lithium metal or other lithium compounds, but it faces challenges in safety and large-scale application. Cathode pre-lithiation, on the other hand, has attracted much attention due to its simple process, high safety, and direct applicability to the existing lithium-ion battery industry.

[0003] Existing cathode-embedded pre-lithiation reagents suffer from poor chemical stability. Upon exposure to air, their crystallinity and electrochemical performance significantly decrease, limiting their practical applications and hindering large-scale production and application. Currently, bulk doping and carbon coating are commonly used to improve the chemical stability and conductivity of pre-lithiation reagents. However, these methods require strict control of ambient humidity during material feeding, and even after battery fabrication, issues such as long formation and charging times and gas generation during high-temperature storage persist. Therefore, there is an urgent need to provide a cathode lithium supplement agent to address the problem of poor chemical stability in existing lithium supplement agent materials, which hinders large-scale production and application. Summary of the Invention

[0004] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, the present invention provides a positive electrode lithium replenishing agent and its preparation method, a positive electrode sheet, and a battery. This positive electrode lithium replenishing agent has the advantages of good chemical stability and can be mass-produced and applied.

[0005] To solve the above-mentioned technical problems, this application is implemented as follows: According to one aspect of this application, an embodiment of this application provides a positive electrode lithium replenishing agent, the positive electrode lithium replenishing agent comprising: The core includes a first lithium replenishing agent, the first lithium replenishing agent comprising a lithium-rich material having an antifluorite structure; A first coating layer is applied to at least a portion of the surface of the core. The first coating layer includes a second lithium replenishing agent, which includes a cobalt-rich lithium-containing material having an anti-fluorite structure. A second coating layer covers at least a portion of the surface of the first coating layer, and the second coating layer comprises a metal compound; The specific capacity of the second lithium replenishing agent is higher than that of the first lithium replenishing agent.

[0006] In some embodiments, the first lithium replenishing agent has the chemical formula Li5Fe. 1-y M y Lithium-rich materials of O4.

[0007] In some embodiments, the second lithium supplement has the chemical formula Li. 5+x Fe 1-x-y-z Co x M y N z Lithium-rich materials of O4.

[0008] In some of these embodiments, the element M includes at least one selected from Al, Ti, Y, V, Nb, W, Zr, La, Mg, Cr, Ge, Mo, Sr, Ca, Ba, Fe, Cu, Zn, Ga, In, Sn, Sb, Ce, and Ta, wherein 0.002 ≤ y ≤ 0.03. The element N includes at least one of Al, Ti, Y, V, Nb, W, Zr, La, Mg, Cr, Ge, Mo, Sr, Ca, Ba, Fe, Cu, Zn, Ga, In, Sn, Sb, Ce, and Ta; Where 0.1≤x≤0.97, 0.002≤y≤0.03, 0.002≤z≤0.03.

[0009] In some of these embodiments, the radius of the positive electrode lithium replenishment core is ≤5 μm.

[0010] In some embodiments, the thickness of the first coating layer of the positive electrode lithium replenisher is 0.3~12μm.

[0011] In some embodiments, the thickness of the second coating layer of the positive electrode lithium replenisher is 1~20 nm.

[0012] In some embodiments, the metal compound includes at least one of a metal oxide, a metal carbide, and a metal nitride.

[0013] In some embodiments, the metal in the metal compound includes at least one selected from Al, Zr, Ti, Mo, Al, Ti, Mg, Nb, and W.

[0014] According to another aspect of this application, embodiments of this application provide a method for preparing a positive electrode lithium supplement, comprising: The first lithium source is mixed with the iron source and the first doping source, and the first lithiation sintering is carried out in an oxidizing atmosphere to obtain the first matrix. The cobalt source, the second lithium source, the second doping source, and the first substrate are sintered together in an oxidizing atmosphere to obtain the second substrate; Under an inert atmosphere, a metal compound is deposited on the surface of the second substrate to obtain the positive electrode lithium replenisher.

[0015] In some embodiments, the first lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium oxide, lithium nitrate, and lithium oxalate.

[0016] In some of these embodiments, the iron source includes at least one of Fe2O3, Fe3O4, FeC2O4, FeO, Fe(NO3)3, FeCl3, and FeSO4.

[0017] In some embodiments, the first doping source includes a first metal oxide and / or a first metal hydroxide.

[0018] In some embodiments, the metal element in the first metal oxide and / or the first metal hydroxide includes at least one of Al, Ti, Y, V, Nb, W, Zr, La, Mg, Cr, Ge, Mo, Sr, Ca, Ba, Fe, Cu, Zn, Ga, Sn, Sb, Ce, and Ta.

[0019] In some of these embodiments, the molar ratio of Li in the first lithium source, Fe in the iron source, and metal in the first doped source is (4.9~5.2):(0.97~0.997):(0.002~0.03).

[0020] In some of these embodiments, the temperature of the first lithiation sintering is 550~850°C, and the time is 3~20h.

[0021] In some embodiments, the second lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium oxide, lithium nitrate, and lithium oxalate.

[0022] In some of these embodiments, the cobalt source includes at least one of cobalt oxide, cobalt hydroxide, cobalt fluoride, cobalt tetroxide, cobalt hydroxyoxide, cobalt carbonate, cobalt sulfate, and cobalt oxalate.

[0023] In some of these embodiments, the second doping source comprises a second metal oxide and / or a second metal hydroxide.

[0024] In some embodiments, the metal element in the second metal oxide and / or the second metal hydroxide includes at least one of Al, Ti, Y, V, Nb, W, Zr, La, Mg, Cr, Ge, Mo, Sr, Ca, Ba, Fe, Cu, Zn, Ga, Sn, Sb, Ce, and Ta.

[0025] In some of these embodiments, the molar ratio of Li in the second lithium source, Co in the cobalt source, metal in the second doping source, and iron in the first matrix is ​​(0.2~10):(0.03~2.6):(0.0002~0.05):(0.34~1).

[0026] In some of these embodiments, the second lithiation sintering temperature is 600~950°C and the time is 2~18h.

[0027] In some embodiments, the method for depositing a metal compound on a second substrate includes atomic deposition.

[0028] In some embodiments, the atomic deposition method includes depositing a vapor carrying a metal compound onto the surface of a second substrate in a vacuum environment using an inert gas at a certain flow rate.

[0029] In some of these embodiments, the atomic deposition temperature is 50-350°C, the carrier flow rate is 30-300 ml / min, the single deposition duration is 55-70 s, and the deposition is repeated 10-100 times.

[0030] In some of these embodiments, a vacuum environment is used when atomically depositing metal compounds.

[0031] According to another aspect of this application, an embodiment of this application provides a positive electrode sheet, including a positive electrode lithium replenishing agent, wherein the positive electrode lithium replenishing agent is the aforementioned positive electrode lithium replenishing agent or a positive electrode lithium replenishing agent prepared according to the aforementioned preparation method.

[0032] According to another aspect of this application, an embodiment of this application provides a battery including a positive electrode, wherein the positive electrode is the aforementioned positive electrode.

[0033] Implementing the technical solution of the present invention has at least the following beneficial effects: In this embodiment, the composition of the cathode lithium supplement is optimized, solving the problems of excessive environmental sensitivity of conventionally used lithium-rich lithium iron phosphate and high cost of using lithium-rich lithium cobalt oxide alone. First, the first coating layer improves the electrochemical performance of the cathode lithium supplement and reduces formation time, thereby increasing battery production efficiency. Second, the lithium-rich lithium cobalt oxide or cobalt-iron miscible lithium oxide phase in the first coating layer enhances the structural stability of the cathode lithium supplement, improves its environmental stability, reduces long-term gas production, and improves its safety performance. Third, the second coating layer further enhances the environmental stability of the cathode lithium supplement.

[0034] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description

[0035] Figure 1 The figure shown is a comparison of the charging curves of coin cells prepared by the positive electrode lithium replenishing agent of Example 3 and Comparative Example 3 of the present invention.

[0036] Figure 2 The image shown is a cross-sectional scanning electron microscope image of the positive electrode sheet further prepared by the positive electrode lithium supplement in Example 1 of the present invention.

[0037] Figure 3 The image shown is a line scan distribution diagram of Co element in the cross-section of the positive electrode lithium replenishment particles in Example 1 of the present invention. Detailed Implementation

[0038] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.

[0039] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges or individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0040] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0041] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0042] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0043] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0044] Currently, the pre-lithiation reagents embedded in the cathode face the critical challenge of insufficient chemical stability in practical applications. These reagents are prone to physicochemical degradation upon exposure to air, primarily manifested as decreased crystallinity and decreased electrochemical performance, severely restricting their large-scale production and application prospects. Although several improvement strategies have been proposed, significant limitations remain: firstly, the process conditions are demanding, requiring a high-quality production and operating environment; secondly, the battery formation and charging processes are time-consuming, affecting production efficiency; and thirdly, gas evolution is prone to occur under high-temperature storage conditions, posing safety and packaging risks. Therefore, there is an urgent need to develop novel pre-lithiation technologies that combine high stability, low environmental sensitivity, and good safety to improve the overall performance of lithium-ion batteries.

[0045] [Cathode Lithium Supplement] Therefore, embodiments of this application provide a positive electrode lithium replenishing agent, the positive electrode lithium replenishing agent comprising: The core includes a first lithium replenishing agent, the first lithium replenishing agent comprising a lithium-rich material having an antifluorite structure; A first coating layer is applied to at least a portion of the surface of the core. The first coating layer includes a second lithium replenishing agent, which includes a cobalt-rich lithium-containing material having an anti-fluorite structure. A second coating layer covers at least a portion of the surface of the first coating layer, and the second coating layer comprises a metal compound; The specific capacity of the second lithium replenishing agent is higher than that of the first lithium replenishing agent.

[0046] The aforementioned "first covering layer covering at least a portion of the surface of the kernel" means that the first covering layer can be disposed on a portion of the surface of the kernel or on the entire surface of the kernel. As in this embodiment, the first covering layer can cover the entire surface of the kernel. This application does not have any particular limitation in this regard, as long as the purpose of this application can be achieved.

[0047] The aforementioned "second covering layer covering at least a portion of the surface of the first covering layer" means that the second covering layer can be disposed on a portion of the surface of the first covering layer or on the entire surface of the first covering layer. As in this embodiment, the second covering layer can cover the entire surface of the first covering layer. This application does not have any particular limitation in this regard, as long as the purpose of this application can be achieved.

[0048] Furthermore, the first coating layer of this application is a cobalt-rich lithium material with an anti-fluorite structure. As the first coating layer of the core (a lithium-rich material with an anti-fluorite structure), it can improve the electronic and ionic conductivity of the material, improve rate performance, reduce the boundary potential, and shorten the formation time, thereby significantly improving the limitations of the material in terms of processing and application performance. At the same time, the phase environment stability and the stability of the delithiated compound of the first coating layer are higher than those of the core. By coating the surface of the cobalt-rich lithium material with an anti-fluorite structure, a lithium-rich lithium cobalt oxide phase or a cobalt-iron miscible phase is formed on the surface of the core, which can further improve the structural stability of the cathode lithium replenishment material, improve the environmental stability of the cathode lithium replenishment material, and reduce the gas generation after long-term use of the cathode lithium replenishment material. In addition, this application provides a metal compound as a second coating layer on the surface of the first coating layer to isolate the positive electrode lithium replenishing agent from the side reactions with water and carbon dioxide in the air, which can further improve the air stability of the positive electrode lithium replenishing agent and solve the defects of existing positive electrode lithium replenishing agents in the positive electrode processing process, which are subject to harsh process conditions and high requirements for production and operating environment.

[0049] Based on the above, this application optimizes the composition of the cathode lithium supplement, solving the problems of excessive environmental sensitivity of conventionally used lithium-rich lithium iron ore and high cost of using lithium-rich lithium cobalt oxide alone. First, the first coating layer improves the electrochemical performance of the cathode lithium supplement and reduces formation time, thereby increasing battery production efficiency. Second, the lithium-rich lithium cobalt oxide or cobalt-iron miscible lithium oxide phase in the first coating layer enhances the structural stability of the cathode lithium supplement, improves its environmental stability, reduces long-term gas production, and improves its safety performance. Third, the second coating layer further enhances the environmental stability of the cathode lithium supplement.

[0050] In some specific embodiments, the first lithium replenishing agent has the chemical formula Li5Fe. 1-y M yLithium-rich materials of O4.

[0051] In some specific embodiments, the second lithium replenishing agent has the chemical formula Li. 5+x Fe 1-x-y-z Co x M y N z Lithium-rich materials of O4.

[0052] In some specific embodiments, the element M includes at least one selected from Al, Ti, Y, V, Nb, W, Zr, La, Mg, Cr, Ge, Mo, Sr, Ca, Ba, Fe, Cu, Zn, Ga, In, Sn, Sb, Ce, and Ta, wherein 0.002 ≤ y ≤ 0.03; The element N includes at least one of Al, Ti, Y, V, Nb, W, Zr, La, Mg, Cr, Ge, Mo, Sr, Ca, Ba, Fe, Cu, Zn, Ga, In, Sn, Sb, Ce, and Ta; Where 0.1≤x≤0.97, 0.002≤y≤0.03, 0.002≤z≤0.03.

[0053] In this application, both the lithium-rich material of the first lithium replenisher and the lithium-rich material of the second lithium replenisher are doped with heterogeneous elements. The doping elements reduce the expansion and contraction of the lattice during the lithium ion extraction and insertion process of the lithium replenisher, suppress irreversible phase transitions and gas generation, improve electronic conductivity and ionic conductivity, optimize the lithium extraction potential plateau, and improve rate performance and lithium replenishment efficiency.

[0054] In some specific embodiments, the radius of the positive electrode lithium replenisher core is ≤5μm, for example, 5μm, 4μm, 3μm, 2μm, 1μm, or any value within the above range. If the core radius of the positive electrode lithium replenisher is too large, for example, >5μm, the diffusion path of lithium ions inside the material increases significantly, resulting in a slower kinetic reaction during charging and an increase in charging potential.

[0055] In some specific embodiments, the thickness of the first coating layer of the positive electrode lithium supplement is 0.3~12μm, for example, 0.3μm, 1μm, 2μm, 4μm, 6μm, 8μm, 10μm, 12μm, or within any two of the above values. Correspondingly, if the thickness of the first coating layer is too high, for example, exceeding 12μm, it will not further improve the electrochemical performance and structural stability of the positive electrode lithium supplement; on the contrary, it will significantly increase the preparation cost of the positive electrode lithium supplement. If the thickness of the first coating layer is too low, for example, below 0.3μm, it is difficult to achieve the effect of improving the electrochemical performance and structural stability of the positive electrode lithium supplement.

[0056] In some specific embodiments, the thickness of the second coating layer of the positive electrode lithium supplement is 1~20nm, for example, 1nm, 3nm, 5nm, 7nm, 9nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm, or within any two of the above values. Correspondingly, if the thickness of the second coating layer is too high, for example, exceeding 20nm, it will hinder the extraction of lithium ions, affecting the rate performance of the battery, and will reduce the specific capacity of the positive electrode lithium supplement, thereby affecting the energy density of the battery. If the thickness of the second coating layer is too low, for example, below 1nm, it cannot completely isolate the side reactions between the positive electrode lithium supplement and water and carbon dioxide in the air, making it difficult to achieve the effect of improving the environmental stability of the positive electrode lithium supplement.

[0057] In this application, the testing methods for the radius of the positive electrode lithium replenishment core, the thickness of the first coating layer, and the thickness of the second coating layer include: mixing the lithium replenishment material and binder in a solvent at a ratio of 95:5 to obtain a slurry; coating the slurry onto a current collector; drying to obtain an electrode sheet; using an argon ion cutter to expose the particle cross-section by argon ions; and performing radial line scanning analysis of the particle cross-section using a scanning electron microscope or transmission electron microscope combined with an EDS spectrometer, with an accelerating voltage of 20 kV. Data are collected equidistantly from the particle surface along the radial direction towards the center. The core radius is the length from the particle center to the point where the Co element signal enhancement occurs; the thickness of the first coating layer is the length from the point where the Co element signal enhancement occurs to the point where the Co element signal clearly disappears; and the thickness of the second coating layer is the length from the point where the second coating element signal enhancement occurs to the particle edge.

[0058] In some specific embodiments, the metal compound includes at least one selected from metal oxides, metal carbides, and metal nitrides. As an example, the metal compound may be a metal oxide or a metal carbide.

[0059] In some specific embodiments, the metal in the metal compound includes at least one selected from Al, Zr, Ti, Mo, Al, Ti, Mg, Nb, and W. As an example, the metal in the metal compound can be Al, Zr, or Ti.

[0060] In some specific embodiments, the particle size Dv50 of the positive electrode lithium replenisher is 3~12μm, for example, 3μm, 5μm, 7μm, 9μm, 11μm, 12μm, or within any two of the above values. Limiting the particle size of the positive electrode lithium replenisher to the above range can significantly improve the charging kinetics performance of the lithium replenisher, increase battery capacity, reduce the shortening of the lithium-ion diffusion path, improve the initial coulombic efficiency, and compensate for lithium loss caused by SEI film formation.

[0061] [Preparation method of positive electrode lithium supplement] Based on the same inventive concept, embodiments of this application provide a method for preparing a positive electrode lithium supplement, including: The first lithium source is mixed with the iron source and the first doping source, and the first lithiation sintering is carried out in an oxidizing atmosphere to obtain the first matrix. The cobalt source, the second lithium source, the second doping source, and the first substrate are sintered together in an oxidizing atmosphere to obtain the second substrate; Under an inert atmosphere, a metal compound is deposited on the surface of the second substrate to obtain the positive electrode lithium replenisher.

[0062] It should be understood that all the features and advantages described above regarding the "positive electrode lithium replenisher" also apply to the "preparation method of the positive electrode lithium replenisher", and will not be repeated here.

[0063] In some specific embodiments, the first lithium source includes at least one selected from lithium hydroxide, lithium carbonate, lithium oxide, lithium nitrate, and lithium oxalate. As an example, the first lithium source can be lithium hydroxide, lithium carbonate, or lithium oxide.

[0064] In some specific embodiments, the iron source includes at least one selected from Fe2O3, Fe3O4, FeC2O4, FeO, Fe(NO3)3, FeCl3, and FeSO4. As an example, the iron source can be Fe2O3 or Fe3O4.

[0065] In some specific embodiments, the first doping source includes a first metal oxide and / or a first metal hydroxide.

[0066] In some specific embodiments, the metal element in the first metal oxide and / or the first metal hydroxide includes at least one selected from Al, Ti, Y, V, Nb, W, Zr, La, Mg, Cr, Ge, Mo, Sr, Ca, Ba, Fe, Cu, Zn, Ga, Sn, Sb, Ce, and Ta. As an example, the metal element in the first metal oxide and / or the first metal hydroxide may be Al, Ti, or Y.

[0067] In some specific embodiments, the molar ratio of Li in the first lithium source, Fe in the iron source, and the metal in the first doped source is (4.9~5.2):(0.97~0.997):(0.002~0.03). As an example, the molar ratio of Li in the first lithium source, Fe in the iron source, and the metal in the first doped source can be 4.9:0.97:0.002, 5:0.98:0.01, 5.2:0.997:0.03, etc., or other ratios within the above range, which are not specifically limited here.

[0068] In some specific embodiments, the temperature of the first lithiation sintering is 550~850℃, and the time is 3~20h. As an example, the temperature of the first lithiation sintering can be 550℃, 650℃, 750℃, 850℃, or any two of the above values. As an example, the time of the first lithiation sintering can be 3h, 5h, 7h, 9h, 11h, 13h, 15h, 17h, 19h, 20h, or any two of the above values.

[0069] In some specific embodiments, the second lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium oxide, lithium nitrate, and lithium oxalate, for example, lithium hydroxide or lithium carbonate.

[0070] In some specific embodiments, the cobalt source includes at least one of cobalt oxide, cobalt hydroxide, cobalt fluoride, cobalt tetroxide, cobalt hydroxyoxide, cobalt carbonate, cobalt sulfate, and cobalt oxalate. For example, it may be cobalt oxide, cobalt hydroxide, or cobalt fluoride.

[0071] In some specific embodiments, the second doping source includes a second metal oxide and / or a second metal hydroxide.

[0072] In some specific embodiments, the metal element in the second metal oxide and / or the second metal hydroxide includes at least one of Al, Ti, Y, V, Nb, W, Zr, La, Mg, Cr, Ge, Mo, Sr, Ca, Ba, Fe, Cu, Zn, Ga, Sn, Sb, Ce, and Ta, for example, it can be Al, it can be Ti, or it can be Y.

[0073] In some specific embodiments, the molar ratio of Li in the second lithium source, Co in the cobalt source, the metal in the second doping source, and iron in the first matrix is ​​(0.2~10):(0.03~2.6):(0.0002~0.05):(0.34~1). For example, the molar ratio of Li in the second lithium source, Co in the cobalt source, the metal in the second doping source, and iron in the first matrix can be 0.2:0.03:0.0002:0.34, 1:1:0.02:0.5, 2.53:1.5:0.03:0.66, 10:2.6:0.05:1, etc., or other ratios within the above range, which are not specifically limited here.

[0074] In some specific embodiments, the temperature of the second lithiation sintering is 600~950℃, for example, 600℃, 700℃, 800℃, 900℃, 950℃ or within any two of the above values; the time is 2~18h, for example, 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h or within any two of the above values.

[0075] In some specific embodiments, the method for depositing the metal compound on the second substrate includes atomic deposition.

[0076] In some specific embodiments, the atomic deposition method includes: depositing a vapor carrying a metal compound onto the surface of a second substrate in a vacuum environment by means of an inert gas at a certain flow rate.

[0077] In some specific embodiments, the atomic deposition temperature is 50~350°C, for example, 50°C, 150°C, 250°C, 350°C, or within any two of the above values; the carrier flow rate is 30~300 ml / min, for example, 30 ml / min, 90 ml / min, 150 ml / min, 210 ml / min, 270 ml / min, 300 ml / min, or within any two of the above values; the single deposition duration is 55~70 s, for example, 55 s, 60 s, 65 s, 70 s, or within any two of the above values; the deposition repetition count is 10~100 times, for example, 10 times, 30 times, 50 times, 70 times, 90 times, 100 times, or within any two of the above values.

[0078] In some specific implementations, a vacuum environment is used when atomically depositing metal compounds.

[0079] In some specific embodiments, the inert gas is at least one of helium, argon, and nitrogen, for example, it can be helium or argon.

[0080] In this application, it should be noted that the first substrate in the preparation process is not equivalent to the core in the product. During the further preparation of the second substrate, a cobalt-rich lithium material with an anti-fluorite structure reacts with the surface material of the first substrate to form a lithium-rich lithium cobalt oxide phase or a cobalt-iron miscible phase. At this point, the unreacted portion of the first substrate constitutes the core of the positive electrode lithium supplement, while the lithium-rich lithium cobalt oxide phase or the cobalt-iron miscible phase and the cobalt-rich lithium material with an anti-fluorite structure form the first coating layer of the positive electrode lithium supplement. Based on the same inventive concept, embodiments of this application provide a battery including a positive electrode sheet, which includes a positive electrode lithium supplement. The positive electrode lithium supplement is the aforementioned positive electrode lithium supplement or a positive electrode lithium supplement prepared according to the aforementioned preparation method. [Positive Electrode Sheet Preparation] The positive electrode material, positive electrode lithium supplement, conductive agent, and binder are mixed in a solvent to obtain a slurry. The slurry is coated onto the current collector and dried to obtain the positive electrode sheet.

[0081] In some specific implementations, the mass ratio of the positive electrode material, the positive electrode lithium replenishing agent, the conductive agent, and the binder is (93~95):(1~3):(1~3):(1~3).

[0082] In some specific embodiments, the current collector includes at least one of aluminum foil or nickel foil.

[0083] In some specific implementations, the coating thickness of the slurry is 10 μm to 200 μm.

[0084] In some specific implementations, after the positive electrode sheet is prepared, it can be cut into the required size by a cutting tool.

[0085] Because the battery contains a positive electrode sheet prepared with the positive electrode lithium replenishing agent provided in the embodiments of this application, it has the advantages of higher energy density, longer cycle life and faster charging speed.

[0086] In some embodiments, the battery further includes a negative electrode, an electrolyte, and a separator. That is, the battery includes a positive electrode, a negative electrode, an electrolyte, and a separator.

[0087] In this embodiment, the materials and structures of the negative electrode current collector, the conductive agent and the binder in the negative electrode active material layer are not limited, and negative electrode structures and components known in the art that can be used in secondary batteries can be selected.

[0088] In this embodiment, the type of separator is not limited, and any separator known in the art that can be used in secondary batteries can be selected.

[0089] It should also be noted that the battery in this application does not limit the specific material or type of electrolyte. Any components and types known in the art that can be used in secondary batteries can be selected, as long as the purpose of this application can be achieved.

[0090] Since the battery provided in this embodiment of the invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, and will not be described in detail here.

[0091] The following describes the implementation methods of this application. The implementation methods described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the implementation methods, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents, materials, or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0092] Example 1 Lithium hydroxide, nano iron oxide, aluminum oxide, and zirconium oxide were weighed and mixed in a mixing machine according to the molar ratio of lithium, iron, aluminum, and zirconium of 5.1:0.98:0.01:0.01. The mixed powder was then placed in a corundum sagger and sintered at 800°C for 12 hours in a nitrogen atmosphere. After being pulverized and sieved, the first matrix was obtained. Lithium hydroxide, the first matrix, nano-cobalt tetroxide, aluminum oxide, and zirconium oxide were weighed and mixed separately according to the molar ratio of lithium, iron, cobalt, aluminum, and zirconium of 0.512:1:0.0809:0.000825:0.000825. The mixture was then placed in a corundum sagger and sintered at 800°C for 8 hours in a nitrogen atmosphere. After being pulverized and sieved, the second matrix was obtained. The second matrix was formed by the partial or complete diffusion and fusion of the first matrix and the first coating layer.

[0093] The second substrate was vibratoryly dispersed and placed into the ALD reaction chamber. A vacuum was drawn and the temperature was raised to 100°C. In this vacuum environment, argon gas at a flow rate of 40 ml / min carried alumina vapor to deposit on the surface of the second substrate particles for 60 seconds. Then, argon gas at a flow rate of 80 ml / min blew away the physically adsorbed alumina from the surface of the second substrate particles, leaving a layer of chemically adsorbed alumina. This process deposited an alumina layer on the surface of the second substrate particles. This cycle was repeated 50 times to obtain the positive electrode lithium replenishment agent. Figure 3 It can be seen that the cobalt element is distributed in a gradient from the surface of the first matrix to the vertical direction near the core.

[0094] Example 2 Lithium hydroxide, nano iron oxide, aluminum oxide, and zirconium oxide were weighed and mixed in a mixing machine according to the molar ratio of lithium, iron, aluminum, and zirconium of 5.1:0.98:0.01:0.01. The mixed powder was placed in a corundum sagger and sintered at 810℃ for 14 hours in a nitrogen atmosphere. After being crushed and sieved, the first matrix was obtained. Lithium hydroxide, the first matrix, nano-cobalt tetroxide, aluminum oxide, and zirconium oxide were weighed and mixed in a mixer according to the molar ratio of lithium, iron, cobalt, aluminum, and zirconium of 1.457:1:0.235:0.0024:0.0024. The mixed powder was placed in a corundum saggar and sintered at a constant temperature of 800℃ for 10 hours in a nitrogen atmosphere. After being pulverized and sieved, the second matrix was obtained.

[0095] The remaining steps are the same as in Example 1.

[0096] Example 3 Lithium hydroxide, nano iron oxide, aluminum oxide, and zirconium oxide were weighed and mixed in a mixing machine according to the molar ratio of lithium, iron, aluminum, and zirconium of 5.1:0.98:0.01:0.01. The mixed powder was placed in a corundum sagger and sintered at 810℃ for 12 hours in a nitrogen atmosphere. After being crushed and sieved, the first matrix was obtained. Lithium hydroxide, the first matrix, nano-cobalt tetroxide, aluminum oxide, and zirconium oxide were weighed and mixed in a mixer according to the molar ratio of lithium, iron, cobalt, aluminum, and zirconium of 2.68:1:0.432:0.00441:0.00441. The mixed powder was placed in a corundum sagger and sintered at a constant temperature of 850℃ for 15 hours in a nitrogen atmosphere. After being pulverized and sieved, the second matrix was obtained.

[0097] The remaining steps are the same as in Example 1.

[0098] Example 4 Lithium hydroxide, nano iron oxide, aluminum oxide, and zirconium oxide were weighed and mixed in a mixing machine according to the molar ratio of lithium, iron, aluminum, and zirconium of 5.1:0.98:0.01:0.01. The mixed powder was placed in a corundum sagger and sintered at 810℃ for 15 hours in a nitrogen atmosphere. After being crushed and sieved, the first matrix was obtained. Lithium hydroxide, the first matrix, nano-cobalt tetroxide, aluminum oxide, and zirconium oxide were weighed and mixed in a mixer according to the molar ratio of lithium, iron, cobalt, aluminum, and zirconium of 6.47:1:1.04:0.0106:0.0106. The mixed powder was placed in a corundum sagger and sintered at a constant temperature of 930℃ for 18 hours in a nitrogen atmosphere. After being pulverized and sieved, the second matrix was obtained.

[0099] The remaining steps are the same as in Example 1.

[0100] Example 5 Lithium hydroxide, nano iron oxide, aluminum oxide, and zirconium oxide were weighed and mixed in a mixing machine according to the molar ratio of lithium, iron, aluminum, and zirconium of 5.1:0.98:0.01:0.01. The mixed powder was placed in a corundum sagger and sintered at 780°C for 15 hours in a nitrogen atmosphere. After being crushed and sieved, the first matrix was obtained. Lithium hydroxide, the first matrix, nano-cobalt tetroxide, aluminum oxide, and zirconium oxide were weighed and mixed separately according to the molar ratio of lithium, iron, cobalt, aluminum, and zirconium of 7.51:1:1.21:0.0124:0.0124. The mixture was then placed in a corundum sagger and sintered at a constant temperature of 720°C for 8 hours in a nitrogen atmosphere. After being pulverized and sieved, the second matrix was obtained.

[0101] The remaining steps are the same as in Example 1.

[0102] Example 6 Lithium hydroxide, nano iron oxide, aluminum oxide, and zirconium oxide were weighed and mixed in a mixing machine according to the molar ratio of lithium, iron, aluminum, and zirconium of 5.1:0.98:0.01:0.01. The mixed powder was placed in a corundum sagger and sintered at 840°C for 15 hours in a nitrogen atmosphere. After being crushed and sieved, the first matrix was obtained. Lithium hydroxide, the first matrix, nano-cobalt tetroxide, aluminum oxide, and zirconium oxide were weighed and mixed separately according to the molar ratio of lithium, iron, cobalt, aluminum, and zirconium of 1.96:1:0.317:0.00323:0.00323. The mixture was then placed in a corundum sagger and sintered at a constant temperature of 850℃ for 12 hours in a nitrogen atmosphere. After being pulverized and sieved, the second matrix was obtained.

[0103] The remaining steps are the same as in Example 1.

[0104] Example 7 Lithium hydroxide, nano iron oxide, aluminum oxide, and zirconium oxide were weighed and mixed in a mixing machine according to the molar ratio of lithium, iron, aluminum, and zirconium of 5.1:0.98:0.01:0.01. The mixed powder was placed in a corundum sagger and sintered at 750°C for 10 hours in a nitrogen atmosphere. After being crushed and sieved, the first matrix was obtained. Lithium hydroxide, the first matrix, nano-cobalt tetroxide, aluminum oxide, and zirconium oxide were weighed and mixed in a mixer according to the molar ratio of lithium, iron, cobalt, aluminum, and zirconium of 3.44:1:0.555:0.00566:0.00566. The mixed powder was placed in a corundum sagger and sintered at a constant temperature of 800℃ for 10 hours in a nitrogen atmosphere. After being pulverized and sieved, the second matrix was obtained.

[0105] The remaining steps are the same as in Example 1.

[0106] Example 8 Lithium hydroxide, nano iron oxide, aluminum oxide, and zirconium oxide were weighed and mixed in a mixing machine according to the molar ratio of lithium, iron, aluminum, and zirconium of 5.1:0.98:0.01:0.01. The mixed powder was placed in a corundum sagger and sintered at 810℃ for 15 hours in a nitrogen atmosphere. After being crushed and sieved, the first matrix was obtained. Lithium hydroxide, the first matrix, nano-cobalt tetroxide, magnesium oxide, and tungsten oxide were weighed and mixed separately according to the molar ratio of lithium, iron, cobalt, magnesium, and tungsten of 6.47:1:1.04:0.0106:0.0106. The mixture was then placed in a corundum sagger and sintered at a constant temperature of 930℃ for 18 hours in a nitrogen atmosphere. After being pulverized and sieved, the second matrix was obtained.

[0107] The remaining steps are the same as in Example 1.

[0108] Example 9 Lithium hydroxide, nano iron oxide, aluminum oxide, and zirconium oxide were weighed and mixed in a mixing machine according to the molar ratio of lithium, iron, aluminum, and zirconium of 5.1:0.98:0.01:0.01. The mixed powder was placed in a corundum sagger and sintered at 810℃ for 15 hours in a nitrogen atmosphere. After being crushed and sieved, the first matrix was obtained. Lithium hydroxide, the first matrix, nano-cobalt tetroxide, aluminum oxide, and zirconium oxide were weighed and mixed in a mixer according to the molar ratio of lithium, iron, cobalt, aluminum, and zirconium of 6.47:1:1.04:0.0106:0.0106. The mixed powder was placed in a corundum sagger and sintered at a constant temperature of 930℃ for 18 hours in a nitrogen atmosphere. After being pulverized and sieved, the second matrix was obtained. The second substrate was vibratoryly dispersed and placed into the ALD reaction chamber. A vacuum was drawn and the temperature was raised to 100°C. In this vacuum environment, argon gas at a flow rate of 40 ml / min carried titanium oxide vapor to deposit on the surface of the second substrate particles for 60 seconds. Then, argon gas at a flow rate of 80 ml / min blew away the physically adsorbed titanium oxide from the surface of the second substrate particles, leaving a layer of chemically adsorbed titanium oxide. This process deposited a layer of titanium oxide on the surface of the second substrate particles. This cycle was repeated 50 times to obtain the positive electrode lithium replenishment agent.

[0109] Example 10 The preparation of the first and second substrates is the same as in Example 8. The second substrate was vibratoryly dispersed and placed into the ALD reaction chamber. A vacuum was drawn and the temperature was raised to 100°C. In this vacuum environment, argon gas at a flow rate of 40 ml / min carried titanium nitride vapor to deposit on the surface of the second substrate particles for 60 seconds. Then, argon gas at a flow rate of 80 ml / min blew away the physically adsorbed titanium nitride from the surface of the second substrate particles, leaving a layer of chemically adsorbed titanium nitride. This process deposited a layer of titanium nitride on the surface of the second substrate particles. This cycle was repeated 50 times to obtain the positive electrode lithium replenishment agent.

[0110] Comparative Example 1 Lithium hydroxide, nano-iron oxide, aluminum oxide, and zirconium oxide were weighed and mixed separately according to the molar ratio of lithium, iron, aluminum, and zirconium of 5.1:0.98:0.01:0.01. The mixture was then placed in a mixer and sintered in a corundum sagger at 800°C for 14 hours in a nitrogen atmosphere. After being pulverized and sieved, the first matrix was obtained. The first matrix was then pulverized and placed in a corundum sagger and sintered at a constant temperature of 800°C for 10 hours in a nitrogen atmosphere. After being pulverized and sieved, the comparative example 1 sample was obtained.

[0111] Comparative Example 2 Lithium hydroxide, nano-iron oxide, aluminum oxide, and zirconium oxide were weighed and mixed separately according to the elemental molar ratio of lithium, iron, aluminum, and zirconium of 5.1:0.98:0.01:0.01. The mixture was then placed in a mixer and the resulting powder was placed in an alumina crucible and sintered at 800°C for 12 hours in a nitrogen atmosphere. After pulverizing and sieving, the first matrix was obtained. Lithium hydroxide, positive electrode lithium supplement core, nano-cobalt tetroxide, aluminum oxide, and zirconium oxide were weighed and mixed separately according to the elemental molar ratio of lithium, iron, cobalt, aluminum, and zirconium of 1.18:1:0.19:0.00194:0.00194. The mixture was then placed in an alumina crucible and sintered at a constant temperature of 700°C for 8 hours in a nitrogen atmosphere. After pulverizing and sieving, the positive electrode lithium supplement was obtained.

[0112] Comparative Example 3 Lithium hydroxide, nano-iron oxide, alumina, and zirconium oxide were weighed and mixed separately according to the elemental molar ratio of lithium, iron, aluminum, and zirconium of 5.1:0.98:0.01:0.01. The mixture was then placed in a mixer and the resulting powder was placed in an alumina crucible and sintered at 820°C for 14 hours in a nitrogen atmosphere. After being pulverized and sieved, the first matrix was obtained. The first matrix was then pulverized and placed in an alumina crucible and sintered at a constant temperature of 850°C for 15 hours in a nitrogen atmosphere. After being pulverized and sieved, the second matrix was obtained. The second matrix was vibrated and dispersed in an ALD reaction chamber, and a vacuum was drawn and the temperature was raised to 100°C. In a vacuum environment, argon gas at a flow rate of 40 ml / min carried alumina vapor and deposited it on the surface of the second matrix particles for 60 seconds. Argon gas at a flow rate of 80 ml / min blew away the physically adsorbed alumina from the surface of the second matrix particles, leaving a layer of chemically adsorbed alumina. This process deposited an alumina layer on the surface of the second matrix particles. Repeat this cycle 50 times to obtain the positive electrode lithium replenishment agent.

[0113] The relevant parameters of the positive electrode lithium replenishing agents prepared in the above embodiments and comparative examples are shown in Table 1.

[0114] Table 1 Test case Button charge capacity test: The positive electrode lithium supplement agent of each embodiment and comparative example was mixed with conductive carbon black SP and binder polyvinylidene fluoride PVDF in a weight ratio of 80%:10%:10% to obtain a positive electrode slurry by dispersion. The slurry was coated on an aluminum foil (13μm thick) current collector and rolled to prepare a positive electrode sheet. Then, the positive electrode sheet was punched into small discs with a diameter of 12mm using a film die, dried and weighed. All processes were carried out in an environment with humidity below 2%. A 2025 coin cell case was used, and a Li metal disc was used as the negative electrode. The coin cell was assembled with the electrolyte and charged at a constant current rate of 0.05C to 4.45V, and then charged at a constant voltage to a cutoff current of 0.02C. The specific capacity obtained was the charging specific capacity.

[0115] 0.05C constant current percentage test: The percentage of constant current charging at 0.05C is equal to the charge capacity at 0.05C / the total charge capacity.

[0116] Charge capacity test after 48 hours: Take 10g of positive electrode lithium replenisher from each embodiment and comparative example, store it in an open container at 50% humidity for 48 hours, and then test the charging capacity after 48 hours according to the button charge capacity test method.

[0117] Gas production test: Preparation of the positive electrode sheet: Lithium iron phosphate (LiFePO4), lithium supplementer, conductive carbon black (SP), and polyvinylidene fluoride (PVDF) binder are thoroughly mixed in an N-methylpyrrolidone solvent system at a weight ratio of 94:2:2:2 to form a uniform positive electrode slurry. This slurry is coated onto an Al foil (the positive electrode current collector), dried, and then cold-pressed to the designed compaction level. The resulting sheets are then slit to obtain the positive electrode sheet. Preparation of the negative electrode sheet: Graphite (the negative electrode active material), conductive carbon, carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) binder are thoroughly mixed in an appropriate amount of water solvent at a weight ratio of 95:2:1.5:1.5 to form a uniform negative electrode slurry. This slurry is coated onto a Cu foil (the negative electrode current collector), dried, and then cold-pressed to the designed compaction level. The resulting sheets are then slit to obtain the negative electrode sheet. Electrolyte preparation: Ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate were mixed in a volume ratio of 1:1:1 and then LiPF6 was added to prepare a 1M solution for use as the electrolyte. Separator preparation: A PE separator was used. Battery preparation: The positive electrode, separator, and negative electrode were stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation, ensuring that the negative electrode film size was larger than the positive electrode size. The positive and negative electrode tabs were welded together to form a bare cell, which was then placed in an outer packaging shell, dried, and injected with electrolyte. Finally, after formation at 45°C and charging to 4.2V, the full battery was obtained after venting, sealing, and subtracting the gas bag capacity. The formation time for Examples 1-10 could be reduced to 4-6 hours, while the formation time for Comparative Examples 1-3 required 8-10 hours to achieve a good formation effect, with the charging specific capacity reaching the coin cell test value. The battery was fully charged to 3.65V using a constant current and constant voltage 1C method, with a cutoff current of 0.05C. Before storage, it was kept in water at 75℃ for 10 minutes, and the test volume was the initial volume V0. The battery was stored in a constant temperature chamber at 75℃, and the volume after 50 days was recorded as V1. The volume growth rate after 50 days was calculated as (V1-V0) / V0×100%.

[0118] The test results for each embodiment and comparative example are detailed in Table 2.

[0119] Table 2 As shown in Table 2, compared with Comparative Examples 1 and 3, Examples 1-10 showed improved charging capacity, reduced polarization and decomposition potential, increased constant current charging ratio, reduced charging capacity decay after 48 hours of storage in a 10% humidity environment, and significantly reduced gas production during high-temperature storage. Examples 1-5 showed that with the increase of Co content, the charging capacity increased, the polarization and decomposition potential decreased, the constant current charging ratio increased, and the gas production during high-temperature storage significantly decreased; the charging capacity decay was not significant after 48 hours of storage in a 10% humidity environment.

[0120] Comparative Example 2, lacking a second coating layer, showed a significant decrease in charge capacity after 48 hours of storage in a 10% humidity environment compared to Example 4. Comparative Example 3, lacking a first coating layer, showed limited improvement in charge capacity, constant current charging ratio, and high-temperature storage gas generation. Furthermore, [the text abruptly ends here]. Figure 1 It can be seen that the charging capacity of Example 3 is improved, the charging potential is reduced by ~0.2V compared with Comparative Example 3, and the proportion of constant charging current is increased by 7.2%.

[0121] Compared with Example 4, Example 8 changed the doping elements from Al and Zr to Mg and W, resulting in a slight increase in the charging capacity. The constant current charging ratio and the charging capacity after 48 hours of storage in a 10% humidity environment showed no significant change, while the gas generation during storage increased slightly.

[0122] Compared with Example 4, Example 9 changed the coating layer from aluminum oxide to titanium oxide, and the charging capacity and constant current ratio were slightly improved; the decrease in charging capacity and storage gas production after 48 hours in a 10% humidity environment did not change significantly.

[0123] Compared with Example 8, Example 10 changed the coating layer from titanium oxide to titanium nitride, which slightly increased the charging capacity and constant current ratio, and reduced storage gas generation; the charging capacity decreased significantly after 48 hours of storage in a 10% humidity environment.

[0124] In addition, by Figure 2 As can be seen, after the coating of the first coating layer in Example 1, the distribution of element Co in the first coating layer in the particles gradually decreases from the surface to the inside of the particles. The first coating layer in Example 1 diffuses to a depth of 2.1 μm from the particle surface to the inside, which can improve the delithiation kinetics and stability of the particle surface, and improve the constant current charging ratio and gas generation.

[0125] The parts of this invention not described in detail are techniques known to those skilled in the art.

[0126] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.

[0127] It should be noted that the terms "and / or" or " / " used herein are merely descriptions of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The singular forms "a," "described," and "the" used in the embodiments of the invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0128] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.

[0129] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode lithium replenishing agent, characterized in that, The positive electrode lithium supplement includes: The core includes a first lithium replenishing agent, the first lithium replenishing agent comprising a lithium-rich material having an antifluorite structure; A first coating layer is applied to at least a portion of the surface of the core. The first coating layer includes a second lithium replenishing agent, which includes a cobalt-rich lithium-containing material having an anti-fluorite structure. A second coating layer covers at least a portion of the surface of the first coating layer, and the second coating layer comprises a metal compound; The specific capacity of the second lithium replenishing agent is higher than that of the first lithium replenishing agent.

2. The positive electrode lithium replenishing agent according to claim 1, characterized in that, The first lithium replenishing agent has the chemical formula Li5Fe 1- y M y Lithium-rich materials for O4; And / or, the second lithium supplement has the chemical formula Li 5+x Fe 1-x-y-z Co x M y N z Lithium-rich materials for O4; The element M includes at least one of Al, Ti, Y, V, Nb, W, Zr, La, Mg, Cr, Ge, Mo, Sr, Ca, Ba, Fe, Cu, Zn, Ga, In, Sn, Sb, Ce, and Ta, wherein 0.002 ≤ y ≤ 0.03; The element N includes at least one of Al, Ti, Y, V, Nb, W, Zr, La, Mg, Cr, Ge, Mo, Sr, Ca, Ba, Fe, Cu, Zn, Ga, In, Sn, Sb, Ce, and Ta; Where 0.1≤x≤0.97, 0.002≤y≤0.03, 0.002≤z≤0.

03.

3. The positive electrode lithium replenishing agent according to claim 1, characterized in that, The positive electrode lithium supplement meets at least one of the following characteristics (1) to (3): (1) The radius of the kernel is ≤5μm; (2) The thickness of the first coating layer is 0.3~12μm; (3) The thickness of the second coating layer is 1~20nm.

4. The positive electrode lithium replenishing agent according to claim 1, characterized in that, The metal compound includes at least one of metal oxides, metal carbides, and metal nitrides; And / or, the metal in the metal compound includes at least one of Al, Zr, Ti, Mo, Al, Ti, Mg, Nb, and W.

5. A method for preparing a positive electrode lithium supplement, characterized in that, The preparation method includes: The first lithium source is mixed with an iron source and a first doping source, and the first lithiation sintering is carried out in an oxidizing atmosphere to obtain the first matrix. The cobalt source, the second lithium source, the second doping source, and the first substrate are sintered together in an oxidizing atmosphere to obtain the second substrate; Under an inert atmosphere, a metal compound is deposited on the surface of the second substrate to obtain the positive electrode lithium replenisher.

6. The method for preparing the positive electrode lithium replenishing agent according to claim 5, characterized in that, The step of preparing the first matrix satisfies at least one of the following features (1) to (5): (1) The first lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium oxide, lithium nitrate and lithium oxalate; (2) The iron source includes at least one of Fe2O3, Fe3O4, FeC2O4, FeO, Fe(NO3)3, FeCl3, and FeSO4; (3) The first doping source includes a first metal oxide and / or a first metal hydroxide; The metal element in the first metal oxide and / or the first metal hydroxide includes at least one of Al, Ti, Y, V, Nb, W, Zr, La, Mg, Cr, Ge, Mo, Sr, Ca, Ba, Fe, Cu, Zn, Ga, Sn, Sb, Ce, and Ta. (4) The molar ratio of Li in the first lithium source, Fe in the iron source, and metal in the first doped source is (4.9~5.2):(0.97~0.997):(0.002~0.03); (5) The temperature of the first lithiation sintering is 550~850℃ and the time is 3~20h.

7. The method for preparing the positive electrode lithium replenishing agent according to claim 5, characterized in that, The step of preparing the second matrix satisfies at least one of the following features (1) to (5): (1) The second lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium oxide, lithium nitrate and lithium oxalate; (2) The cobalt source includes at least one of cobalt oxide, cobalt hydroxide, cobalt fluoride, cobalt tetroxide, cobalt hydroxyoxide, cobalt carbonate, cobalt sulfate, and cobalt oxalate; (3) The second doping source includes a second metal oxide and / or a second metal hydroxide; The metal element in the second metal oxide and / or the second metal hydroxide includes at least one of Al, Ti, Y, V, Nb, W, Zr, La, Mg, Cr, Ge, Mo, Sr, Ca, Ba, Fe, Cu, Zn, Ga, Sn, Sb, Ce, and Ta. (4) The molar ratio of Li in the second lithium source, Co in the cobalt source, metal in the second doped source, and iron in the first matrix is ​​(0.2~10):(0.03~2.6):(0.0002~0.05):(0.34~1); (5) The second lithiation sintering temperature is 600~950℃ and the time is 2~18h.

8. The method for preparing the positive electrode lithium replenishing agent according to claim 5, characterized in that, The method for depositing metal compounds on a second substrate includes atomic deposition. The atomic deposition method includes: depositing a vapor carrying a metal compound onto the surface of a second substrate in a vacuum environment using an inert gas at a certain flow rate; The atomic deposition temperature is 50~350℃, the carrier flow rate is 30~300ml / min, the single deposition duration is 55~70s, and the deposition repetition number is 10~100 times; Atom deposition of metallic compounds occurs in a vacuum environment.

9. A positive electrode sheet, comprising a positive lithium supplement agent, characterized in that, The positive electrode lithium replenishing agent is the positive electrode lithium replenishing agent according to any one of claims 1 to 4 or the positive electrode lithium replenishing agent prepared by the preparation method according to any one of claims 5 to 8.

10. A battery, comprising a positive electrode, characterized in that, The positive electrode is the positive electrode as described in claim 9.